INVESTIGATING THE LEVEL OF FIRE SAFETY AT PRISONS IN HUNGARY - HORVÁTH, Péter; KALAMÁR, Norbert (Studia Universitatis Babeș-Bolyai Ambientum, 2018)
In Hungary fire-fighting duties are generally fulfilled by fire services operating within the framework of the unified organization of disaster management. To increase efficiency this might change in specific cases, furthermore other organisations can also fulfill fire-fighting duties. The reason behind this is that sometimes fire-fighters arrive at the scene with a considerable delay therefore people located in the area have to start fire-fighting with the utilization of special equipment to minimize damage. Such occasions are when disasters or fires are to be managed during mass events, affrays or inside prisons. Method: The author applied the current legislation of Hungary, interviewed some of the managers working in the Prison Service as well as utilized his previous experience in fire-fighting. The study describes the current state of the Hungarian prisons, depicts the characteristics and the current changes of the fire safety training received by the prison personnel. Are shown examples regarding cases where the arrival of fire-fighters cannot be achieved under the professionally accepted time limit of 15 minutes. A cell fire with a fatal outcome is also described in the paper. The complicated situation faced by the prison personnel in case of fire is also addressed. The author tries to assist in the improvement of the educational syllabus as well as in the perfecting of the knowledge of the personnel.